Certain properties of ω-Q-fuzzy subrings - Dilshad Alghazzawi; Wafaa H. Hanoon; Muhammad Gulzar; Ghazanfar Abbas; Nasreen Kausar (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In this paper, we define the fuzzy subring and discussed various fundamental aspects of fuzzy subrings. We introduce the concept of level subset of this new fuzzy set and prove that level subset of fuzzy subring form a ring. We define fuzzy ideal and show that set of all fuzzy cosets form a ring. Moreover, we investigate the properties of homomorphic image of fuzzy subring.